Computer reconstruction and analysis of the vermiform mollusc Acaenoplax hayae from the Herefordshire Lagerstatte (Silurian, England), and implications for molluscan phylogeny - Sutton, MD; Briggs, D; Siveter, D; Siveter, D (2004)
Acaenoplax hayae is a spinose worm-like animal from the Silurian Herefordshire Lagerstätte of England, a deposit that preserves high-fidelity soft-part morphology of invertebrates in three dimensions. Specimens have been serially ground and reconstructed by computer to their three-dimensional form. Acaenoplax bears serially repeated transverse ridges dorsally, each with an array of probably aragonitic spines inclined posteriorly. Oblique ventral loberows correspond in position to the dorsal ridges. Aragonitic dorsal valves overlie every third ridge; the penultimate valve is absent leaving a total of seven. The anterior termination is disk-like, surrounding an antero-medial mouth. At the posterior termination there is a cavity between the posteriormost dorsal and a posteroventral valve, from which soft-part projections extend. Acaenoplax is interpreted as a creeping epibenthic animal that fed on sessile prey. It is an 'aculiferan' mollusc, combining unique autapomorphic structures with characters typical of the Polyplacophora and Aplacophora. Its morphology can be accommodated within both of the competing schemes of molluscan phylogeny, and its closest living relatives in both cases are aplacophorans. The highly serialized morphology of Acaenoplax is unique within the Mollusca, but the pattern it highlights is an attractive candidate for the primitive state of serial repetition within the phylum. © The Palaeontological Association.